Diagnostic and Therapeutic Problems of Geriatric Headache - Kaviyan Ghandehari; Seyed Hadi Akhbari (University of Social Welfare & Rehabilitation Sciences, 2007)
There is no difference in clinical characteristics of headache between old individuals and younger’s. However, differential diagnosis of migrainous aura and transient ischemic attacks may be difficult in old people who frequently have vascular risk factors. Old people have less headache than the young’s. Chronic tension headache is the most common primary type of headache in the elderly. Chronic paroxismal hemicrania and headache due to giant cell arterities are specified to the elderly, Secondary headaches; e.g headache due to cervical spondylosis and brain tumors is more common in the old people than young. Old people poorly tolerate headache drugs, i.e. Ergotamine, Triptans and Tricyclics. Trigeminal neuralgia is often seen in the elderly and is resistant to medical therapy in the old people. Headache could be the main manifestation of depression in old people. Headaches secondary to disorders of internal medicine; i.e. hypertension and chronic obstructive pulmonary disease have importance in the elderly. Subarachnoid hemorrhage is considered in every old person with sudden onset explosive headache especially in cases with decreased consciousness and neck stiffness. Old individuals use a collection of different drugs due to suffering various diseases and commonly have drug induced headaches. Neuroimaging should be performed in a geriatric patient with new onset sever headache without medical disorder or consumption of drug induced headache. Some of the old people suffer of multiple types of headache.